2020
DOI: 10.1111/sji.12920
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of marginal zone B cells in pathophysiological processes

Abstract: The maintenance of inner integrity of an organism is founded on the proper performance of two immunity branches, innate and adaptive immune responses. Recently, it became apparent that subset of splenic B cells named marginal zone B cells (MZB cells) exhibits unique developmental and functional features that bridge these two immunity branches. Strategically positioned at the site where blood and lymph are filtered, MZB cells represent a population of sentinels that rapidly proliferate and differentiate into Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 128 publications
(183 reference statements)
0
9
0
1
Order By: Relevance
“…The top term enriched for the ɛ2‐associated genes was the quantity of marginal‐zone B (MZB) lymphocytes (Figure 3A). It is believed that MZB cells mainly produce immunoglobulin M antibodies and may regulate autoimmunity 65,66 . The MZB cells play their vital role in the early antibody reaction to pathogens by mobilizing an optimal response of the innate and adaptive immune systems 67,68 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top term enriched for the ɛ2‐associated genes was the quantity of marginal‐zone B (MZB) lymphocytes (Figure 3A). It is believed that MZB cells mainly produce immunoglobulin M antibodies and may regulate autoimmunity 65,66 . The MZB cells play their vital role in the early antibody reaction to pathogens by mobilizing an optimal response of the innate and adaptive immune systems 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that MZB cells mainly produce immunoglobulin M antibodies and may regulate autoimmunity. 65,66 The MZB cells play their vital role in the early antibody reaction to pathogens by mobilizing an optimal response of the innate and adaptive immune systems. 67,68 Although B cells may have a neuroprotective effect by producing immunoglobulins against amyloid beta (Aβ), 69 murine AD models show that B cells may also influence the formation of Aβ plaques through deposition of immunoglobulins and appear to be enriched in the AD brains.…”
Section: Snpsmentioning
confidence: 99%
“…Interestingly, MZ B-cells have also been shown to migrate to T-cell zones of secondary lymphoid organs and activate CD4 + T-cells [ 46 ]. Additionally, MZ B-cells are able to present antigens to invariant natural killer T-cells (iNKT), a type of NKT-cell with a restricted TCR repertoire that can recognize lipidic molecules in the context of atypical MHC class I-like molecules of the CD1 family, widely expressed by MZ B-cells [ 47 , 48 ]. These MZ: iNKT cellular interactions confer activation, notably via the CD40-CD40L pathway [ 48 ].…”
Section: Mz B-cells and Their Antibody Responsesmentioning
confidence: 99%
“…36,42 This subset of B lymphocytes is also involved in the generation of immune tolerance, and dysregulation of MZ B cells has been implicated in the pathophysiology of autoimmune diseases like systemic lupus erythematosus. 45,46 There is growing evidence that MZ B cells could be targeted for treatment of cancer and infectious diseases. 47 For example, a previous study has shown that it is possible to elicit a systemic anti-tumor T cellular response in mice after intravenous administration of NPs that selectively deliver tumor-associated antigens to splenic MZ B cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Also, within the spleen, CART-2 more efficiently delivered mRNA to splenic MZ B cells and NK cells compared to CART-1 , which could be particularly important from a therapeutic standpoint. MZ B cells play a significant role as APCs in starting both humoral and cellular immune responses against bloodborne antigens. , This subset of B lymphocytes is also involved in the generation of immune tolerance, and dysregulation of MZ B cells has been implicated in the pathophysiology of autoimmune diseases like systemic lupus erythematosus. , There is growing evidence that MZ B cells could be targeted for treatment of cancer and infectious diseases . For example, a previous study has shown that it is possible to elicit a systemic anti-tumor T cellular response in mice after intravenous administration of NPs that selectively deliver tumor-associated antigens to splenic MZ B cells …”
Section: Resultsmentioning
confidence: 99%